GUARDIANS OF THE CONSTITUTION OR ENGINEERS OF CHAOS? CHALLENGES AND PERSPECTIVES OF LAW IN PAPUA NEW GUINEA - Edstron S. Santos, Júlio (Revista Gênero e Interdisciplinaridade, 2026)
This research analyzes constitutionalism in Papua New Guinea (PNG) as a unique laboratory of legal pluralism in the Global South, investigating the constitutive tension between the Westminster state model and Melanesian oral tradition. This research is justified by its critical relevance to peripheral democracies, illustrating the limits of legal monism in fragmented societies. Methodologically, it adopts a qualitative and functional comparative approach, contrasting PNG’s legal architecture (unitarianism, advisory jurisdiction) with the Brazilian system (federalism, diffuse control). The work examines the genesis of the 1975 “Home-Grown” Constitution, the Judiciary structure, and existential challenges such as the “resource curse” and Bougainville’s independence. It concludes that PNG experiences “Creative Constitutional Uncertainty,” wherein the Judiciary transcends law application to act as a governance design thinker, arbitrating the traumatic transition between tradition and market. The system demonstrates resilience through legal syncretism where the “Underlying Law” seeks to decolonize justice, negotiating sovereignty with local structures.